Thermodynamic modeling of the Mo–Ni system. (September 2018) - Yaqoob, Khurram; Crivello, Jean-Claude; Joubert, Jean-Marc
Abstract: Thermodynamic stability of the MoNi2 and MoNi8 compounds has been discussed in detail, and decision about their inclusion in thermodynamic assessment of the Mo–Ni system has been made. Enthalpies of formation of all Mo–Ni intermetallic compounds have been determined with the help of DFT calculations whereas enthalpies of mixing in the solid solutions are estimated using special quasi-random structures. Experimental phase equilibria information gathered in our recent partial investigation of the Mo–Ni system has been incorporated and thermodynamic reassessment of the Mo–Ni system has been performed with the help of the CALPHAD method. The calculated Mo–Ni phase diagram showed good agreement with selected experimental information. Highlights: New DFT calculations (formation and mixing enthalpies) have been performed. The existence of the MoNi2 and MoNi8 phases have been discussed in detail. Thermodynamic reassessment of the Mo–Ni system has been carried out. A minimum number of fitting parameters was used.